High Level of Cellulase and β-Glucosidase Production by T.reesei and T.koningii Combinations on Corn Straws of Alkali Pretreatment. Issue 3 (August 2013) - Yang, Peizhou; Luo, Shuizhong; Zheng, Zhi; Jiang, Shaotong; Guo, N.A.; Cheng, Jieshun
In order to obtain high level of β-glucosidase and filter paper activity production, the screening of strain combinations and the characteristic of enzymes from co-culture were investigated. The results showed that both the β-glucosidase (0.347 U/ml) and FPA (3.21 U/ml) reached the highest level via co-culture of T.reesei and T.koningii with the corn straw of alkali pretreatment as fermentation substrate. After 72 h of fermentation, both two enzyme activities reached the highest level. And the optimal temperature and pH value were 55°C and 5.5, respectively. These two enzyme stability decreased rapidly when the temperatures exceeded 90°C. The conversion efficiency reached 0.652 g reducing sugar per g pretreated corn straw using the enzymes from these two fungi, which was 1.49-fold and 1.64-fold compared with those from T.reesei (0.439 g/g) and T.koningii (0.398 g/g). The present work demonstrated an effective way to develop an efficient system for the bioconversion of agricultural waste straws to sugar.